Development Of Picture And Letter Poster Media To Improve The Ability To Recognize Pictures And Letters In Young Children - Nana Maryana; Alfauzan Amin (Utan Kayu Publishing, 2025)
Produce flannel letter board media for early childhood, animal themes to improve the language skils of early childhood group B in TKK Salvatoris Satap SDI Soka, South Golewa District. Ngada Regency, (2) knows the quality of the results of the flannel letter board media product trials on animal themes for early childhood group A at TKK Salvatoris Satap SDI Soka. This letter flannel board media was developed with the ADDIE model. This model consists of five parts, namely: (1) analize, (2) design, (3) development, (4) implementation, and (5) evaluation. Theresults of research on the development of letter flannel board media based on the results of expert trials and early childhood as product users are as follows: (1) media expert trials are in the valid category, (2) material expert trials are categorized as very valid, (3) expert design trials with valid categories, (4) small group trials with valid categories, (5) individual trials with very valid categories. Thus, based on the results of the flannel board media trial results for AUD by experts that it is feasible to use in the learning